Remarkable sexually dimorphic Aroidothrips longistylus newly recorded from China (Thysanoptera: Thripidae) - Tong, Xiaoli; Wang, Zhaohong; Zhao, Chao (Zootaxa, 2015)
Sexual dimorphism is a phenotypic differentiation between males and females of the same species. Thrips display a wide variety of sexual dimorphism between taxa including size, ornamentation and coloration (Crespi 1986, Mound 2005, Tyagi et al. 2008). During recent surveys on the thrips fauna in subtropical China, Aroidothrips longistylus Ananthakrishnan, an interesting and little known sexually dimorphic species, was found. This discovery greatly extends the geographic distribution of this species that has been known only from South India (Tyagi et al. 2008).